Java 9 new features deep dive - Verhas, Peter; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Java 9 intends to change the way Java developers used to write code. It introduces a modular JDK so that developers can only include the modules that they need. The prospect of being one of the first to explore the brand new JDK from Java is the primary motivator. Also, this is the biggest change that has been introduced in Java for a while. The primary motivator for this video is to see it as a preparatory course for what's to come in Java 9. We will emphasize the impact new features will have on development, and of course get the viewer actually writing out their own Java 9 code examples too. We will start up with the setting up of Java 9 and learn the modularization concepts and then proceed to deployment. This should be hands on look at Java 9, but no one will be using it to make real-world applications yet. This is an assessment video for the millions of Java developers out there looking to put it to the test. "--Resource description page.
Presenter, Peter Verhas.
Title from title screen (viewed August 11, 2017).
Date of publication from resource description page.
Keywords: Java (Computer program language); Electronic books